Comparison of H∞, H2, and pole optimization for power system oscillation damping with remote renewable generation. Issue 27 (2016) - Mešanović, Amer; Münz, Ulrich; Heyde, Chris
Abstract: This paper presents a comparison between H ∞, H 2, and pole optimization to damp active power oscillations in a power system. We use the DC power flow equations to describe the transmission grid, and generator dynamics are represented with swing equations. As a test case, we consider active power oscillation damping, with virtual inertia and damping provided by geographically remote renewable generators. In the end, optimization results of the different methods are compared.